Evolusi Normatif Peran Penanggung Jawab Proyek Kerjasama (PJPK) dalam Skema Kerjasama Pemerintah dan Badan Usaha (KPBU) : Rekonstruksi Hukum dalam Tata Kelola Penyelenggaraan Infrastruktur Berkelanjutan di Indonesia - Shannia Angelia Rahardjo; Muhamad Farudin (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
Infrastructure development has become a national priority to drive economic growth, with the KPBU (Public-Private Partnership) scheme as a solution to budget limitations. The transformation of PJPK (Project Implementing Agency) law in the latest regulations, including the authority of the Rector of State Universities with Legal Entity (PTN BH) and restrictions on the Board of Directors of Regional-Owned Enterprises (BUMD), demonstrates the policy dynamics that influence the effectiveness of infrastructure management based on KPBU in Indonesia. This research uses a normative juridical method with legislative and conceptual approaches to analyze regulations and legal theories related to the role of PJPK in KPBU. This approach aims to provide a strong argumentative foundation and a comprehensive analysis of the legal aspects in the implementation of infrastructure based on KPBU. This article emphasizes that the regulatory reform of the PJPK role in KPBU aims to enhance efficiency, accountability, and legal certainty. With the latest regulations, the role of PJPK becomes clearer, accelerating sustainable infrastructure projects and creating a more conducive investment environment for the private sector.